The role of Muhammad Iqbal and Ali Bey Huseynzade in the formation of national identity among Indian and Azerbaijani Muslims - Mammadova, Turkan (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article discusses the common peculiarities of two eastern thinkers Ali bey Huseynzade (1864-1940) and Muhammad Iqbal (1877-1936). The main aim of the article is the investigation of the role of Ali Bey Huseynzade and Muhammad Iqbal in the formation of national identity among Indian and Azerbaijani muslims. The article argues that the political thoughts, speeches, and literary works of both thinkers served to form their nations and establish the independent national states. The first part of the article dedicated to achieving the formation of national identity through an Islamic revival. Both thinkers consider that it is possible to create conditions for a bright future for Muslims by restoring the former power of Islam. The second part devoted to the views of thinkers on the formation of a strong society through the application of Western science. The struggle to end colonial dependence and to benefit from scientific achievements of Europe at the same time were their main missions. Their contribution to the establishment of national independent states has been strongly studied in the third part of the article. As a result of the influence of Ali Bey and Iqbal, two independent states were formed in the East. Islamic values played an important role in the establishment of both states. In conclusion, the article once again emphasizes the contributions of both Eastern thinkers.